Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-74959-0
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and economical effect of application biostimulants containing seaweed extracts and amino acids as an element of agroecological management of bean cultivation

Abstract: The implementation of agronomic activities, based on the use of biostimulants, is an important element of agroecological practices. Therefore, comprehensive research was carried on the use of biostimulants. A field experiment was performed in 2016–2018 with common bean of Mexican Black cultivar. In particular growing seasons, bean plants were treated with Kelpak SL (seaweed extracts) and Terra Sorb Complex (free amino acids) in the form of single and double spraying with two solutions concentrations. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 82 publications
4
30
0
Order By: Relevance
“…The effects of usage of biostimulants can be attributed to the induction of the activity of phenylalanine ammonia-lyase enzyme, which is an essential regulator in the phenols synthesis pathway [27]. Natural extracts can enhance the anthocyanin and phenolic content in crops as a result of the modulation of genes involved in the anthocyanin and flavonoid biosynthesis pathway [96].…”
Section: Total Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of usage of biostimulants can be attributed to the induction of the activity of phenylalanine ammonia-lyase enzyme, which is an essential regulator in the phenols synthesis pathway [27]. Natural extracts can enhance the anthocyanin and phenolic content in crops as a result of the modulation of genes involved in the anthocyanin and flavonoid biosynthesis pathway [96].…”
Section: Total Phenolic Compoundsmentioning
confidence: 99%
“…Initially, biostimulants were applied in organic production, but nowadays, they are also used in conventional and integrated crop production [22]. The most widely used bio-products are based on amino acids, algal extracts, and humic compounds [27].…”
Section: Introductionmentioning
confidence: 99%
“…Among available classes, the biostimulants based on protein hydrolysates and the products containing amino acids are particularly worthy of attention because they enhance plant yield and quality in terms of growth, phytochemical content, N-uptake, and tolerance to many abiotic stresses [ 21 , 23 , 25 , 26 ]. Recent researches have specifically demonstrated that biostimulants can improve the nutritional traits of some plant-derived foods by enhancing the accumulation of secondary metabolites and phytonutrients in different parts of the plant [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Basie et al [208] review how biostimulants from different sources have been applied to fruit trees, grapevines and berry crops against abiotic stress, including drought and salinity. In an interesting field experiment, Kocira et al [209] used foliar treatments of seaweed-or amino-acid-based biostimulants. Both increased yield, but the profits using seaweed extracts are higher in comparison to amino acids: EUR 752.57•ha −1 to EUR 119.67•ha −1 , respectively (Figure 4).…”
Section: Biostimulants' Field Applicationsmentioning
confidence: 99%